Negative regulatory roles of ORMDL3 in the FcεRI-triggered expression of proinflammatory mediators and chemotactic response in murine mast cells - Bugajev, Viktor; Halova, Ivana; Draberova, Lubica; Bambouskova, Monika; Potuckova, Lucie; Draberova, Helena; Paulenda, Tomas; Junyent, Sergi; Draber, Petr (Cellular and molecular life sciences, 2016)
Single-nucleotide polymorphism studies have linked the chromosome 17q12-q21 region, where the human orosomucoid-like (ORMDL)3 gene is localized, to the risk of asthma and several other inflammatory diseases. Although mast cells are involved in the development of these diseases, the contribution of ORMDL3 to the mast cell physiology is unknown. In this study, we examined the role of ORMDL3 in antigen-induced activation of murine mast cells with reduced or enhanced ORMDL3 expression. Our data show that in antigen-activated mast cells, reduced expression of the ORMDL3 protein had no effect on degranulation and calcium response, but significantly enhanced phosphorylation of AKT kinase at Ser 473 followed by enhanced phosphorylation and degradation of IκBα and translocation of the NF-κB p65 subunit into the nucleus. These events were associated with an increased expression of proinflammatory cytokines (TNF-α, IL-6, and IL-13), chemokines (CCL3 and CCL4), and cyclooxygenase-2 dependent synthesis of prostaglandin D2. Antigen-mediated chemotaxis was also enhanced in ORMDL3-deficient cells, whereas spreading on fibronectin was decreased. On the other hand, increased expression of ORMDL3 had no significant effect on the studied signaling events, except for reduced antigen-mediated chemotaxis. These data were corroborated by increased IgE-antigen-dependent passive cutaneous anaphylaxis in mice with locally silenced ORMDL3 using short interfering RNAs. Our data also show that antigen triggers suppression of ORMDL3 expression in the mast cells. In summary, we provide evidence that downregulation of ORMDL3 expression in mast cells enhances AKT and NF-κB-directed signaling pathways and chemotaxis and contributes to the development of mast cell-mediated local inflammation in vivo.
Keywords: kultivované buňky; membránové proteiny; messenger RNA; receptory IgE; Up-Regulation; Mice, Inbred BALB C; Receptors, IgE; Mast cell; mastocyty; Membrane Proteins; upregulace; RNA interference; cytokiny; down regulace; Mice; Cytokines; ORMDL3 knockdown; Chemotaxis; degranulace buněk; Down-Regulation; Cells, Cultured; Prostaglandin D2; RNA, Messenger; zvířata; myši inbrední BALB C; myši; Mast Cells; chemotaxe; Cell Degranulation; Degranulation; Proinflammatory cytokines; Animals